STRATEGI KOMUNIKASI BISNIS DALAM ARUS KOREAN WAVE: STUDI KASUS CHINGU CAFÉ BANDUNG - Meyla Tazqiya Rakhma; Vellyana Paraswati (Universitas Tidar, 2025)
The Korean Wave in Indonesia has transcended its role as an entertainment trend and evolved into a lifestyle phenomenon that significantly influences consumer behavior, particularly in the culinary sector. This study aims to analyze cross-cultural communication strategies employed by Chingu Café, a Korean-themed restaurant in Bandung, in shaping consumer perception and loyalty. A descriptive qualitative method was applied, utilizing observation, literature review, and content analysis of social media as primary data sources. The findings reveal that Chingu Café successfully integrates both verbal and non-verbal communication in building a consistent brand identity. The use of the Korean term “Chingu” as the brand name, menu items presented with original Korean terminology, interior design featuring Hangul and K-pop elements, as well as greetings in Korean by staff, all serve as cultural cues reinforcing the authenticity of the brand. Moreover, cultural adaptation through halal certification and affordable pricing plays a crucial role in establishing consumer trust and accessibility. The study concludes that the success of thematic culinary businesses relies not only on product quality but also on effective and contextual cross-cultural communication. Future research should further explore the role of digital media in strengthening cultural perceptions and conduct comparative studies with other country-themed restaurants to gain a broader understanding of cultural acculturation dynamics in Indonesia’s culinary industry .